Crude Cell-Free Extract From Deinococcus radiodurans Exhibit Anticancer Activity by Inducing Apoptosis in Triple-Negative Breast Cancer Cells - Maqbool, Illiyas; Sudharsan, M.; Kanimozhi, G.; Alrashood, Sara T.; Khan, Haseeb A.; Prasad, Nagarajan Rajendra (Frontiers in Cell and Developmental Biology, 2020)
Extremophilic organisms have the potential to tolerate extremely challenging environments of nature. This property can be accredited to its production of novel secondary metabolites that possess anticancer and other pharmaceutical values. The present study was aimed to investigate the anticancer activity of crude secondary metabolites extract (CSME) obtained from the radiation-tolerant bacterium Deinococcus radiodurans in triple-negative human breast carcinoma (MDA-MB-231) cells. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay showed the antiproliferative potential of CSME in MDA-MB-231 cells (IC50 = 25 µg/ml) and MCF-7 cells (IC50 = 10 µg/ml). Further, the CSME treatment led to the production of intracellular reactive oxygen species (ROS) and nuclear membrane alterations with the formation of apoptotic bodies in MDA-MB-231 cells. Considerable DNA damage and low antioxidant status were observed in CSME treated MDA-MB-231 cells. The results also showed that the CSME treatment induced apoptotic markers expression in MDA-MB-231 cells. Western blot results illustrated significant upregulation of p53, caspase-3, and caspase-9 protein expression. Then, we analyzed the presence of secondary metabolites which may be linked with the antiproliferative potential of CSME by gas chromatography-mass spectrometry (GC-MS). The results illustrated the presence of twenty-three bioactive compounds some of which are already reported to possess anticancer properties. The study indicates that the CSME of D. radiodurans possess anticancer properties and exhibit the potential to be used as an anticancer agent.